Tingkat Inovasi sebagai Strategi Pengembangan Produk Usaha Kecil Menengah di Desa Kebonharjo - Heri Nurranto; Fajar Kurniadi; Askardiya Mirza Gayatri (Sosio e-Kons, 2019)
This study aims to determine the level of product innovation and the obstacles faced by small businesses of palm sugar producers and etawa goat milk farmers in Kebonharjo Village, Samigaluh District, Kulonprogo Regency. The method used in this study is a qualitative research method and a sequential explanatory descriptive approach. The sample of the study was 75 people consisting of 54 palm sugar producers and 21 etawa goat milk breeders in Kebonharjo Village, Samigaluh District, Kulonprogo Regency. The analytical approach uses index numbers, the result is a product innovation index of 31.80 palm sugar producers and etawa goat milk farmers 13.14. The constraints faced by small-scale business actors are not focused on running a business, the way of production has passed both ways and development, geographical conditions, motivation for business development is relatively lacking, production capacity depends on the availability of natural resources, capital, distribution and marketing access, patterns of substantive economic activities and comparative advantages that make people feel comfortable.